Dispersal of Insect at Honitetu Forest in West Seram District - Fransina Latumahina; Cornelia Wattimena; Gabriella Mattinahoru (CV. Literasi Indonesia, 2021)
The research objective was to determine the spread of insect species in educational forests and the diversity and abundance of insects. The research was carried out in the Educational Forest of ​​Honitetu in May - June 2020 using the method of drawing sample plots in ​​3 hectares, then an observation path was made using the path method for insect inventory and systematic sampling for vegetation inventory with the plot size. 20 m wide, 100 m long with a distance between lines of 20 m. Insects were collected using hand-collecting and pitfall trap methods at a distance of 10 m and bait traps every 10 m. The results of the study found 6462 insects consisting of 62 species in 12 orders, are Coleoptera, Hymenoptera, Orthoptera, Diptera, Blattaria, Hemiptera, Lepidoptera, Phasmatodea, Opiliones, Araneae, Mantodea in 35 families, namely Chrysomelidae, Cerambycidae, Formicidae, Apidae, Calliphoridae, Tettigoniidae, Acrididae, Grylludae, Blaberidae, Pentatomidae, Piesmatidae, Culicidae, Carabidae, Alydidae, Nanomatidae, Eresidae, Vespidae, Asilidae, Zodaridae, Buprestidae, Phasmatidaal, Blattidae, Platypezidae, Sarcophidae, Noctuidae, Rhaphidophoridae, Sclerosomatidae, and Ichneumonidae. Most species found from the Order Hymenoptera Family Formicidae and the most diminutive species found are the Order Lepidoptera Family Danaidae, Papilionidae, Nymphalidae, Order Hymenoptera Family Braconidae, and Order Opiliones Family Sclerosomatidae. The maximum H 'value is 4.127, the evenness index of 0.628 is classified as moderate, and the dominance index is 0.111 and is classified as low.